(untitled) (Docentes 2.0 Journal, 2020)
Adstract In today’s world, companies dedicated to production, within their processes, there is noise, rotating shifts, physical effort, repetitive movements, heat, work under pressure, among others, which makes it possible to appear psychosocial risk factors positively affecting or negatively to the workers in the execution of their jobs, if the level of stress in the workers is moderate, it positively affects the fact that it forces them to strive to be better every day fulfilling their responsibilities and their lifestyle, on the other hand if the The level of stress is in excess, it negatively affects the worker, by not meeting the quality standards in the production processes or presenting a damage in the operation of the machinery, due to any lack of knowledge, which means an unscheduled stop in the production processes, of It also represents large economic losses. This makes it possible to generate a level of stress in workers who are engaged in the extraction of African palm oil in the canton of La Concordia. The present investigation is of a quantitative transversal type through the application of the questionnaires of free use of the battery of the Ministry of Social Protection, in a production company that is dedicated to the extraction of African palm oil, this company presents high levels of stress, in the domains, both intra-labor and extra-labor, the amount of symptoms and their frequency of presentation is indicative of a severe stress response and harmful to health. The most critical and frequent symptoms require immediate intervention within the framework of an epidemiological surveillance system. The intra-labor and extra-labor risk factors also present a significant picture for their stress effect, in the most relevant domains we have an economic situation of the family group, it is evident that 32% of the workers present economic difficulties, this makes it possible to have an effect on the increase of stress in the workers, in the same way the influence influence of the extra-labor environment, the problems, or domestic calamities with their relatives affect the well-being and the labor activity of the worker generating the increase of the level of stress of the worker.